Pengaruh Tingkat Pengangguran dan PDRB Terhadap Kemiskinan di Provinsi Banten Periode Tahun 2017-2021 - Arina Dian Puspita (Sekolah Tinggi Ilmu Administrasi Yappi Makassar Jl. Sumba no 46, Kota Makassar, Sulawesi Selatan, 2022)
This study aims to analyze the effect of the unemployment rate and GRDP on poverty in Banten Province from 2017 to 2021 and identify areas with lagging economic growth and advanced economic growth. In this analysis, another goal to examine is the reason why an area in Banten Province has lagging economic growth. Also, this study aims to design a policy direction for increasing economic growth in Banten Province within a period of five years. This study uses the Panel Data method. Utilization of analytical tools in this study will be used to see and determine which areas have lagging economic growth and which areas have advanced economic growth in Banten Province. In addition, the analysis tools in this study will also provide an explanation of things that can or should be improved in order to increase economic growth in Banten Province.